Deconstructing Fahr's disease/syndrome of brain calcification in the era of new genes - Batla, Amit; Balint, Bettina (Parkinsonism & related disorders, 2017)
Introduction: There are now a number genes, known to be associated with familial primary brain calcification (PFBC), causing the so called ‘Fahr's’ disease or syndrome. These are SCL20A2, PDGFB, PDGFRB and XPR1. In this systematic review, we analyse the clinical and radiological features reported in genetically confirmed cases with PFBC. We have additionally reviewed pseudohypoparathyroidism which is a close differential diagnosis of PFBC in clinical presentation and is also genetically determined. Methods: We performed a Medline search, from 1st Jan 2012 through to 7th November 2016, for publications with confirmed mutations of SCL20A2, PDGFB, PDGFRB, and XPR1 and found twenty papers with 137 eligible cases. A second search was done for publications of cases with Pseudohypoparathyroidism or pseudopseudohypoparathyroidism, and found 18 publications with 20 eligible cases. Results: SLC20A2 was the most common gene involved with 75 out of 137 cases included with PFBC (55%) followed by PDGFB (31%) and PDGFRB (11%). Statistically significant correlation was found between the presence of parkinsonism with SLC20A2 mutations, headache in PDGFB and generalised tonic-clonic seizures in patients with pseudohypoparathyroidism. Conclusion: We combine statistical analysis and clinical inference to suggest a diagnostic algorithm based on the observations in this study to help with investigation of a patient with neurological features and brain calcification.